Lower Zinc but Higher Calcium Content in Rodent Spinal Cord Compared to Brain - Alma I. Santos-Díaz; Brandon Bizup; Ana Karen Pantaleón-Gómez; Beatriz Osorio; Olivier Christophe Barbier; Thanos Tzounopoulos; Fanis Missirlis (Cells, 2025)
Metal ion measurements using inductively coupled plasma optical emission spectroscopy revealed twofold-higher zinc content in rat brain compared to spinal cord. One hypothesis to explain this difference is the high prevalence of synapses that corelease glutamate and zinc in the brain, marked by the vesicular Zinc Transporter-3 (ZnT3). In contrast, spinal cord tissue showed significantly higher calcium content, reflecting calcifications in the arachnoid. The above observations were made in 60-day-old adult male and female rats fed ad libitum or a restricted diet. In this study, we asked if the calcium and zinc content of the brain and spinal cord was species-specific or evolutionarily conserved, and whether the distinct concentration of zinc in the brain and spinal cord resulted from a different expression pattern of ZnT3, the primary transporter in synaptic vesicles. To address these questions, we examined 8-week-old wild-type male and female mice raised under conventional laboratory conditions and used a knock-in mouse that expresses a human influenza hemagglutinin epitope tag at the C terminus of the endogenous ZnT3 gene to assess the transporter’s abundance in spinal cord sections. Our results show conserved inverse differences in zinc and calcium content in mouse brain and spinal cord, but detectable ZnT3 signal in spinal cord. Whereas vesicular zinc modulates glutamatergic and GABAergic signaling and sensory processing, the functional significance of calcium aggregates in the arachnoid remains unknown.